Hierarchical synthesis of silver monoliths and their efficient catalytic activity for the reduction of 4-nitrophenol to 4-aminophenol. (10th June 2016) - Bano, Mustri; Ahirwar, Devendra; Thomas, Molly; Naikoo, Gowhar Ahmad; Sheikh, Mehraj Ud-Din; Khan, Farid
Abstract : Epoch-making catalytic activities of silver monoliths against the reduction of 4-NP to 4-AP and their industrial importance. Abstract : A novel catalyst Ag/Triton X-705/SiNPs is synthesized by a modified sol–gel method without the use of an acid or a base as a catalyst for the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) in the presence of 0.1 M NaBH4 in aqueous media. The reduction time was found to be 30–35 seconds when the concentration of 4-NP was varied from 0.001 M to 0.009 M while maintaining a constant amount of the Ag/Triton X-705/SiNP catalyst at 0.006 g. Fe3 O4 NPs, dextran, and trimethylbenzene (TMB) were added separately to Ag/Triton X-705 hydrogels to modify their morphology and catalytic activities against the reduction of 4-NP to 4-AP. The as-synthesized monoliths were characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), powder X-ray diffraction (PXRD) analysis, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Brunauer–Emmett–Teller (BET) surface area analysis. The pseudo first order rate constant ( k ), energy of activation ( E a ), and thermodynamic parameters viz. activation enthalpy (Δ H ‡ ), activation Gibbs free energy (Δ G ‡ ) and entropy of activation (Δ S ‡ ) have also been determined. The turnover frequency (TOF) of the Ag/Triton X-705/SiNP catalyst was 9.66 × 10 20 molecules per s and the catalyst was used up to nine cycles successfully with greater efficiency, making it a potential and leading candidate for the industrial conversion of 4-NP to 4-AP. We claimed that the Ag/Triton X-705/SiNP catalyst took almost minimum time for the reduction of 4-NP to 4-AP.